The role of culture in quality improvement in the intensive care unit: a literature review - Soh, Kim Lam; Soh, Kim Geok; Davidson, Patricia M. (Sciedu Press, 2013)
Improving the quality of patient care and patient outcomes is a major concern internationally. In a developing health care system, implementing quality improvement is challenging due not only to resource and workforce issues but also cultural factors. Using the method of a focussed literature review, this paper discusses the importance of assessing a societal view of culture, social mores and customs, and power relationships in quality improvement activities using the intensive care unit as an exemplar. We conclude that implementing quality improvement strategies in a developing health care system needs to address the broader perspectives of social and cultural systems particularly hierarchical relationships and issues of non-disclosure.